Labor Market Institutions and Wage Inequality in the OECD countries - Victoria Sparrman; Ellen Marie Rossvoll (Statistics Norway, Research Department, 2015)
In this paper we attempt to investigate the effect on income inequality of some recent trends in the labour market, changes in regulations of temporary positions and the surge in immigration in many EU-countries. The empirical results show that less strict regulations of temporary positions and higher immigration increase income inequality. The effects of other labour market institutions, such as tax and benefit replacement ratio, on wage inequality are mainly in line with previous literature, but our results are based on a larger sample size in both the time and country dimension. The empirical analysis is conducted on panel data for 20 OECD countries between 1973 and 2011. We perform two robustness checks to our results. First, we account for indirect effects of changes in labor market institutions on wage inequality via the unemployment rates. The indirect effects suggest that labour market institutions have a larger effect on wage inequality than before. Second, we account for cross-sectional dependence and the results point at lower but significant effects of most of the labour market institutions on wage inequality.
Keywords: E24; J08; J31; J51; 330; Inflation modelling; pattern wage bargaining; inflation targeting; dynamic econometrics; cointegration; small open economy